Analysis Of The Effect Of Rainfall On The Corrosion Rate Of Car Frames In 10 Regions In Indonesia That Have High Rainfall Levels - arvian enggal putra; togu juliman manulang; stepeen binsar manurung; willy brodus nimo; Fardin Hasiubuan (Universitas Riau Kepulauan, 2026)
This study aims to understand how much rainfall affects damage (corrosion) to car frames in 10 regions in Indonesia that are often hit by heavy rain. The car's frame is essential for the strength and safety of the vehicle, but it can be severely damaged by corrosion. In Indonesia, which has a tropical climate with high rainfall, rainwater can accelerate corrosion because it acts as a